Mulberry Posterior Inferior Nasal Turbinate Is Associated with a Lower Pharyngeal pH Environment - Javorská, Zuzana; Zeleník, Karol; Lukáčová, Kristína; Taimrová, Renata; Vrtková, Adéla; Hránková, Viktória; Lubojacký, Jakub; Formánek, Martin; Tedla, Miroslav (The Laryngoscope, 2024)
OBJECTIVES: Mulberry-like changes of the posterior inferior nasal turbinate (MPINT) can lead to nasal obstruction. Extraesophageal reflux (EER) characterized by lower pH causes mucosal inflammation and therefore can contribute to sinonasal pathologies. No prior studies have objectively examined the possible association between acidic pH and MPINT formation. Therefore, this study is aimed to investigate the 24-h pharyngeal pH value in patients with MPINT. STUDY DESIGN: Prospective case-control multi-center study. METHODS: Fifty-five patients with chronic EER symptoms were included in the study. They filled in questionnaires aimed at reflux and sinonasal symptoms (RSI®, SNOT-22) and underwent video endoscopy evaluating the laryngeal findings (RFS®) and the presence or absence of the MPINT. And, 24-h oropharyngeal pH monitoring was used to detect the acidic pH environment in the pharynx. RESULTS: Out of the 55 analyzed patients, 38 had the MPINT (group 1), and in 17 patients, the MPINT was absent (group 2). Based on the pathological RYAN Score, in 29 (52.7%) patients, severe acidic pH drops were detected. In group 1, the acidic pH drops were diagnosed significantly more often (68.4%) compared with those in group 2 (p = 0.001). Moreover, in group 1, a significantly higher median total percentage of time spent below pH 5.5 (p = 0.005), as well as a higher median number of events lasting more than 5 min (p = 0.006), and higher median total number of events with pH drops (p = 0.017) were observed. CONCLUSION: In this study, the MPINT was significantly more often present in patients with acidic pH events detected by 24-h oropharyngeal pH monitoring. Acidic pH in the pharynx might lead to MPINT formation. LEVEL OF EVIDENCE: 3 Laryngoscope, 134:62-68, 2024.
Keywords: Pharynx; nosní skořepy; gastroezofageální reflux; koncentrace vodíkových iontů; Morus; Hydrogen-Ion Concentration; lidé; farynx; Humans; Gastroesophageal Reflux; Turbinates